MANAGEMENT PENANGANAN FISIOTERAPI PADA KASUS POST ORIF FEMUR DEXTRA EC. FRAKTUR FEMUR DEXTRA DI PKU BANTUL YOGYAKARTA - Widya Rustikarini; Totok Budi Santoso; Anas Pradana (Bajang Institute, 2023)
Introduction : Fracture is a condition that occurs when the integrity and strength of the bone is damaged due to invasive disease or a damaging biological process. around the bone is the determinant of whether the fracture is complete or incomplete. Purpose: of this study is to determine the implementation of physiotherapy in overcoming pain reduction in cases of post orif femur dextra ec. fracture of the right femur. Methods: active exercise, passive exercise, ankle pumping, static quadriceps, early mobilization of the patient is given for 4 weeks. Results: evaluation was carried out using ROM (Range of Motion,), Manual Muscle Testing, anthropometry and Numeric Rating Scale. Conclusion: there is an increase in ROM (Range of Motion,), Manual Muscle Testing, anthropometry and Numeric Rating Scale for 4 weeks.